2010
DOI: 10.4314/njsr.v6i1-2.54784
|View full text |Cite
|
Sign up to set email alerts
|

Report of six cases of metastatic jaw tumours in Nigerians

Abstract: Background: Metastatic tumours make up approximately one per cent of all oral malignancies. Such tumours may present in the jawbones and oral soft tissues. The commonest oral site is the mandible. Nigerian reports of metastatic tumours to the jaws are very rare. Method: This is a retrospective study of six cases of metastatic tumours to the jaws seen at the Maxillofacial Unit, Ahmadu Bello University Hospital, Kaduna from1979-1998,representing 1% of all histologically confirmed malignant jaw tumours in the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The treatment option and prognosis depends upon site of origin and degree of metastatic spread. In a study conducted by Adebayo and Ajike, 19 of 24 cases (79%) of oral metastatic tumors died within 12 months of diagnosis which attributed to the poor prognosis of oral metastasis [ 10 ]. Treatment modalities include surgical resection, radiation, chemotherapy, or a combination of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment option and prognosis depends upon site of origin and degree of metastatic spread. In a study conducted by Adebayo and Ajike, 19 of 24 cases (79%) of oral metastatic tumors died within 12 months of diagnosis which attributed to the poor prognosis of oral metastasis [ 10 ]. Treatment modalities include surgical resection, radiation, chemotherapy, or a combination of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Radiographic findings in metastatic tumors to the jaw may range from the absence of any manifestation to a lytic or opaque lesion with ill-defined margins. In general, the balance between osteoblastic and osteoclastic activity determines the phenotype of metastatic bone lesions.…”
Section: Pathogenesismentioning
confidence: 99%
“…Tamiolakis et al in the year 2007 explained that the red bone marrow is believed to be necessary for the establishment and proliferation of metastases and they also reported that the metastatic occurrence in the mandible bone is not common as the red marrow is scanty in the matured mandible. 2 Scolozzi et al in 2006 reported that the increased blood flow in the inflamed gingival region may serve as the fertile place for the proliferation of the engulfed tumor cells. 5 A remarkable drawback exist during histopathalogical examination of the metastasized tumor as the specimen contains only poorly differentiated tumor cells, which is challenging to determine the type and location of the primary tumor.…”
Section: Oral Metastasis As the First Manifestation Of An Extragonadamentioning
confidence: 99%
“…3 Particular attention and knowledge, to diagnose and differentiate the oral lesion before arriving to a conclusion, is mandatory to every clinician. 2,4 It has commonly happened in majority of cases that primary tumor is left undiagnosed at the time of metastasized jaw tumor is presented and diagnosed. 5 Regarding this case, the primary carcinoma was not developed either in the placenta or in the uterus (germinomatous).…”
Section: Oral Metastasis As the First Manifestation Of An Extragonadamentioning
confidence: 99%
See 1 more Smart Citation